Using Resources Strategically to Create Wealth - Singh, Suneet (2012)
The sports industry in India is an industry with tremendous potential and is still considered to be at a developing stage at the present moment. The Indian sports sector is often looked upon as an underdeveloped sector and has always been suppressed when compared to other developed sectors like textile, automobile etc., which are deemed as an asset or a vital ingredient in a country’s growth. Today in India when stress and tension are talking its toll on professional and personal lives of people, they are looking to indulge themselves in various sports and leisure activities to stay fit and have an active life style. India has a population of over 1.2 billion people and have of this population is below the age of twenty five. The growing awareness of people in sports and recreational activities has pushed public and private companies to diversify their portfolios and get into the sports sector. As per Times of India reports, revenue from the sports sector would be close to $2 billion at the end of year 2014. However even after these pleasing figures India’s sports business is still just 1.3% of the global revenue from sports which is close to $145.3 billion. Anyone without even having knowledge of Indian sports would know that much of the money in sports is based on the national passion for Cricket. The launch of the IPL (Indian Premier League) was a massive boost to the amount of revenue spent around sports. In recent months there have been recent developments like the inaugural formula one grand prix and the successfully hosted commonwealth games that suggest that other sports are starting to become serious propositions in this sector.